Effectiveness of Platelet Transfusion in Dengue Fever Patients: A Systematic Review - Desyarni, Ninu; Triyanto, Endang (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Dengue fever is a global health concern characterized by severe thrombocytopenia and an increased risk of bleeding. Platelet transfusion is often used to manage thrombocytopenia, but its effectiveness remains uncertain. This review aims to evaluate the efficacy of platelet transfusion in preventing bleeding and improving clinical outcomes among dengue fever patients. A systematic search was conducted across PubMed, ScienceDirect, and Google Scholar using keywords such as “platelet transfusion,” “dengue fever,” and “thrombocytopenia.” Nine studies, including randomized controlled trials and observational studies, were analyzed for outcomes related to bleeding incidence, platelet recovery, and hospitalization duration. The findings indicate that prophylactic platelet transfusion does not significantly reduce bleeding incidence or improve recovery rates in dengue patients. It may be associated with delayed platelet recovery, prolonged hospitalization, and increased risk of adverse events. Keywords: Dengue Fever, Platelet Transfusion, Thrombocytopenia, Bleeding, Hospitalization.